PERBANDINGAN AKTIVITAS SPESIFIK EKSTRAK KASAR ENZIM BROMELIN BUAH NANAS YANG DIISOLASI DENGAN BEBERAPA JENIS GARAM PENGENDAP - Kusuma, I. A. Preharsini; Laksmiwati, A. A. I. A. M.; Arsa, Made; Ratnayani, Ketut (Jurnal Kimia (Journal of Chemistry); Vol. 9, No. 2 Juli 2015, 2015)
The aim of this research was to find specific activity of bromelain enzyme extracted from crude extract of pineapple fruit (Queen variety) by salting out method using three different salts, which were (NH 4 ) 2 SO 4 , NaCl, and Kusamba traditional salt. Crude extract of bromelain enzyme was obtained by precipitation method using salt with different levels of saturation. This study included determination of total protein concentration by using Biuret method and protease activity by using Anson method to get the specific activities of the crude extract. The results showed that the highest specific activities of bromelain enzymes precipitated with the three salts (NH 4 ) 2 SO 4 , NaCl and Kusamba traditional salt with the ratio of 1: 0.94: 0.56 were 0.2887 U/mg (at 20% saturation) ; 0.2705 U/mg (at 40% saturation) and 0.1623 U/mg (at 80% saturation). Fractination of enzyme with the NaCl and Kusamba traditional salt gave smaller specific activity value than (NH 4 ) 2 SO 4. This results may caused of NaCl had smaller ionic strength, the presence of other ions in Kusamba traditional salt and the different solubility of bromelain enzyme in different salts. However, due to the ratio of NaCl approached (NH 4 ) 2 SO 4 and the availability of Kusamba traditional salt they could be used as alternative salts to replace (NH 4 ) 2 SO 4 in fractination bromelain enzyme from crude extract of pineapple fruit
Keywords: pineapple fruit, bromelain enzyme, salting out, specific activity